PROFIL HASIL BELAJAR SISWA PADA MATERI PERBANDINGAN MELALUI PENGGUNAAN MODEL QUANTUM TEACHING DI KELAS VII SMP NEGERI 6 AMBON - Lewier, Ferly; Tutuhatunewa, Edith; Mataheru, Wilmintjie (Jurnal Pendidikan Matematika (JUPITEK), 2018)
The aim of this study is to describe the profile of student learning outcomes in theproportion material using Quantum Teaching model. This type of research is Classroom Action Research. The research subjects were students of grade VII9 of SMP Negeri 6 Ambon. This research data is in the form of learning outcomes tests (quantitative data) and observation sheets of teacher and student activities (qualitative data). Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed by reducing data, describing data, and concluding data. This study produced a profile of student learning outcomes, namely in the first cycle, there were 7 students (24.13%) completed and 22 students (75.87%) were not completed while in the second cycle, there were 23 students (79.31%) completed and 6 students (20.68%) have not completed